2022
DOI: 10.1128/spectrum.00741-22
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Confer Resistance to Azithromycin in Shigella in Bangladesh: a Comprehensive Whole Genome-Based Approach

Abstract: Shigella can frequently transform into a superbug due to uncontrolled and rogue administration of antibiotics and the emergence of HGT of antimicrobial resistance factors. The advent of AZM resistance in Shigella has become a serious concern in the treatment of shigellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In the current study, we found sharp increase of AZM-resistance after 2014 and mphA gene was the key mechanism of resistance. Interestingly, in one of our recently published studies, we reported for the rst time of macrolide resistance pKSR100 when the plasmid carrying IS26-mphA-mrx-mphR(A)-IS6100 in Shigella isolated in Bangladesh the years after 2014 47 .…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, we found sharp increase of AZM-resistance after 2014 and mphA gene was the key mechanism of resistance. Interestingly, in one of our recently published studies, we reported for the rst time of macrolide resistance pKSR100 when the plasmid carrying IS26-mphA-mrx-mphR(A)-IS6100 in Shigella isolated in Bangladesh the years after 2014 47 .…”
Section: Discussionmentioning
confidence: 97%
“…A IncFII type plasmid pKSR100 is the most crucial genomic entity fostering AZM resistance 35 , 52 . We reported for the first time of macrolide resistance pKSR100 when the plasmid carrying IS26– mph A –mrx–mph R(A)–IS6100 in Shigella isolated in Bangladesh the years after 2014 53 .…”
Section: Discussionmentioning
confidence: 99%
“…60 In the gene cluster mphA-mrx(A)-mphR(A) for high-level macrolide inactivation, mphA encodes a phosphotransferase that inactivates erythromycin and mrx(A) encodes a protein required for expression of MphA, whereas MphR(A) encoded by mphR(A) negatively regulates the expression of mphA at the transcriptional level. 61 The IS26-mph(A)-mrx(A)-mph(R)(A)-IS6100 unit, which is linked to the global dissemination of macrolideresistance genes, 62 is the most common form in plasmids carrying mphA. 63 Class 1 integrons are prevalent genetic elements that play a key role in the spread of antibiotic resistance, 64 allowing bacteria to capture and exchange ARGs embedded in the gene cassettes.…”
Section: Discussionmentioning
confidence: 99%